Evidence supports blind screening for internal malignancy in dermatomyositis: Data from 2 large US dermatology cohorts. Issue 2 (January 2018) - Leatham, Hayley; Schadt, Courtney; Chisolm, Sarah; Fretwell, Deborah; Chung, Lorinda; Callen, Jeffrey P.; Fiorentino, David
Abstract : Abstract: The association between dermatomyositis and internal malignancy is well established, but there is little consensus about the methods of cancer screening that should be utilized. We wished to analyze the prevalence and yield of selected cancer screening modalities in patients with dermatomyositis. We performed a retrospective analysis of 2 large US dermatomyositis cohorts comprising 400 patients. We measured the frequency of selected screening tests used to search for malignancy. Patients with a biopsy-confirmed malignancy were identified. Prespecified clinical and laboratory factors were tested for association with malignancy. For each malignancy we identified the screening test(s) that led to diagnosis and classified these tests as either blind (not guided by suspicious sign/symptom) or triggered (by a suspicious sign or symptom). Forty-eight patients (12.0% of total cohort) with 53 cancers were identified with dermatomyositis-associated malignancy. Twenty-one of these 53 cancers (40%) were diagnosed within 1 year of dermatomyositis symptom onset. In multivariate analysis, older age ( P = .0005) was the only significant risk factor for internal malignancy. There was no significant difference in cancer incidence between classic and clinically amyopathic patients. Twenty-seven patients (6.8% of the total cohort) harbored an undiagnosed malignancy at the time of dermatomyositis diagnosis. The majority (59%) of these cancers were asymptomatic and computed tomography (CT) scans were the most common studies to reveal a cancer. This is the largest US cohort studied to examine malignancy prevalence and screening practices in dermatomyositis patients. Our results demonstrate that, while undiagnosed malignancy is present in <10% of US patients at the time of dermatomyositis onset, it is often not associated with a suspicious sign or symptom. Our data suggest that effective malignancy screening of dermatomyositis patients often requires evaluation beyond a history, physical examination, and "age-appropriate" cancer screening—these data may help to inform future guidelines for malignancy screening in this population. Abstract : Supplemental Digital Content is available in the text